1990
DOI: 10.1093/infdis/161.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Responses to Pneumocystis carinii Antigens in Health and Disease

Abstract: Serum antibodies to human Pneumocystis carinii antigens were measured in greater than 400 specimens from different population groups by the immunoblotting technique. Serologic responses varied during the first 2 years of life, but in children greater than or equal to 2 1/2 years and in adults antibodies to a 40-kDa band were found in greater than 85% of the specimens; antigens to bands of 66, 92, and 116 kDa were also detected frequently. The prevalence of serum antibodies in immunosuppressed patients varied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
1
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(134 citation statements)
references
References 60 publications
5
127
1
1
Order By: Relevance
“…P neumocystis carinii is an opportunistic fungal pathogen that affects predominantly immunocompromised hosts including those with AIDS (1). P. carinii pneumonia (PCP) 3 remains the most frequently reported serious opportunistic infection in AIDS patients and the second highest cause of mortality among persons with AIDS in the U.S., despite the availability of effective chemoprophylaxis (2). Primary P. carinii infection is not common because immunocompetent individuals develop Ab to P. carinii by 2-3 years of age (3).…”
Section: Neonatal T Cells In An Adultmentioning
confidence: 99%
See 1 more Smart Citation
“…P neumocystis carinii is an opportunistic fungal pathogen that affects predominantly immunocompromised hosts including those with AIDS (1). P. carinii pneumonia (PCP) 3 remains the most frequently reported serious opportunistic infection in AIDS patients and the second highest cause of mortality among persons with AIDS in the U.S., despite the availability of effective chemoprophylaxis (2). Primary P. carinii infection is not common because immunocompetent individuals develop Ab to P. carinii by 2-3 years of age (3).…”
Section: Neonatal T Cells In An Adultmentioning
confidence: 99%
“…P. carinii pneumonia (PCP) 3 remains the most frequently reported serious opportunistic infection in AIDS patients and the second highest cause of mortality among persons with AIDS in the U.S., despite the availability of effective chemoprophylaxis (2). Primary P. carinii infection is not common because immunocompetent individuals develop Ab to P. carinii by 2-3 years of age (3). Recently, it has been reported that there is a relatively high incidence of P. carinii infection in autopsy specimens of children who die from sudden infant death syndrome.…”
Section: Neonatal T Cells In An Adultmentioning
confidence: 99%
“…Seroepidemiological data, obtained using several antigens, indicate that primary infection by Pneumocystis organisms is one of the most frequent infections in humans, affecting more than 90 % of normal healthy children during the first 2 years of life (Meuwissen et al, 1977;Peglow et al, 1990;Pifer et al, 1978;Vargas et al, 2001;Wakefield et al, 1990a). However, only a small amount of information is available about the infection source and the clinical or pathological changes associated with this first contact with the fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Ces patients porteurs colonisés par le micromycète sont habituellement identifiés par la positivité de la PCR (polymerase chain reaction) Pneumocystis pratiquée sur un prélèvement respiratoire, alors que l'examen microscopique est néga-tif et que les signes cliniques et radiologiques de pneumocystose sont absents [6]. Ainsi, P. jirovecii peut être détecté chez des sujets apparemment sains, adultes et enfants (ces derniers développant dans plus de 90 % des cas une primo-infection par P. jirovecii avant l'âge de 4 ans) [7]. Les femmes enceintes, les patients sous corticoïdes, immunodéprimés, atteints de maladies systémiques ou encore de maladies pulmonaires chroniques comme la bronchopneumopathie chronique obstructive (BPCO) peuvent également être colonisés par le champignon [6].…”
Section: Les Espèces De Pneumocystis Sont Activement Transmises Par Vunclassified